1976
DOI: 10.1002/1097-0142(197603)37:3<1417::aid-cncr2820370324>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

The effect of radiation therapy on lymphocyte subpopulations in cancer patients

Abstract: The proportion of T and B lymphocytes in the peripheral blood was determined in patients with either mammary cancer or with various pelvic malignancies. In cancer patients studied prior to irradiation the level of cells forming either E-rosettes or EAC'-rosettes was similar to that found among healthy controls. Radiation therapy resulted in a striking lymphopenia. The level of cells with T-cell markers was diminished to a greater extent than the level of cells with B-cell markers. T h e relative proportion of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
4

Year Published

1977
1977
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(33 citation statements)
references
References 9 publications
3
26
0
4
Order By: Relevance
“…No bizarre opportunistic infections were seen but one totally anergic patient with Stage IVB disease (lymphocyte-depleted (Gross, Manfredi and Protos, 1973;Chee, Illberg and Rickinson, 1974;Raben et al, 1976) and chemotherapy (review Harris et al, 1976) may depress immunity, but the improvement in the patients' general condition following remission of the malignancy may result in normal or improved immune function (Sokal and Primikirios, 1961;Young et al, 1972). In patients with Hodgkin's disease studied 5 years after completing radical radiotherapy, no gross defects in immunity were found (Kun and Johnson, 1975).…”
Section: Resultsmentioning
confidence: 99%
“…No bizarre opportunistic infections were seen but one totally anergic patient with Stage IVB disease (lymphocyte-depleted (Gross, Manfredi and Protos, 1973;Chee, Illberg and Rickinson, 1974;Raben et al, 1976) and chemotherapy (review Harris et al, 1976) may depress immunity, but the improvement in the patients' general condition following remission of the malignancy may result in normal or improved immune function (Sokal and Primikirios, 1961;Young et al, 1972). In patients with Hodgkin's disease studied 5 years after completing radical radiotherapy, no gross defects in immunity were found (Kun and Johnson, 1975).…”
Section: Resultsmentioning
confidence: 99%
“…31 Publications from the 1960s and 1970s noted the development of severe lymphopenia after radiation in patients with brain, breast, cervical, uterine, and lung cancers without the use of concurrent chemotherapy or glucocorticoids. 13,14,16,17,32 The radiation oncologists reporting these results expressed concerns that radiation-induced injury to the immune system could negatively affect patient outcomes, but no attempts were made to correlate posttreatment lymphopenia with survival. Nonetheless, accumulating data suggested that postradiation lymphopenia could result from the irradiation of circulating lymphocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Radiation therapy itself has historically been associated with post-treatment lymphopenia in a wide range of cancers, including in gynecologic neoplasms [17–20]. Recent studies have identified an association between post-treatment lymphopenia and decreased survival in patients with solid tumors who underwent radiation therapy, irrespective of histology, lymphotoxic chemotherapy regimens and/or corticosteroid administration [2125].…”
Section: Introductionmentioning
confidence: 99%